EXPLORING THE ROLE OF FOOD AID PROGRAMS IN STRENGTHENING RESILIENCE AMONG PASTORALIST COMMUNITIES IN KAJIADO COUNTY - Lekasi , Stephen Oseur; Odek, Antony Wando (American International Journal of Social Science Research, 2025)
Drought is one of the most prevalent natural hazards that pose a threat to food security as well as pastoral livelihoods in Kenya and Africa in general. This research explores the contribution of food aid interventions towards enhancing the resilience of pastoralist communities within Kajiado County. Based on Social-Ecological Resilience and Political Ecology principles, the research investigated the impact of food aid on household food security, livelihood diversification, and adaptation dynamics in response to recurring droughts. The research employed qualitative methods with 25 purposively selected key informants and included household representatives, leaders, and local authority members. The data were collected through focus group discussions, in-depth interviews, and key informant interviews and analyzed using themes. The implications are that, while food relief is critical in the short term for drought survival, it makes little contribution to long-term livelihood diversification except in combination with complementary assistance like skills training, micro-grants, or agricultural inputs. Most diversification activities, such as charcoal production, bead making, and spontaneous trade, were driven by necessity rather than organized assistance. Food aid was also described as irregular, poorly targeted, and insufficient for sustainable economic transformation in similar terms. The study concludes that food assistance to be effective in promoting resilience needs to move from reactive relief to development programming. The study calls for the need to  connect assistance with vocational training, market access, as well as structural inequality mitigation, specifically the one being encountered by women. The aforementioned interventions are necessary to the emergence of adaptive, autonomous pastoral societies.